2016
DOI: 10.1007/s00216-016-9502-3
|View full text |Cite
|
Sign up to set email alerts
|

Label-free C-reactive protein electronic detection with an electrolyte-gated organic field-effect transistor-based immunosensor

Abstract: In this contribution, we propose a label-free immunosensor, based on a novel type of electrolyte-gated field-effect transistor (EGOFET), for ultrasensitive detection of the C-reactive protein (CRP). The recognition layer of the biosensor is fabricated by physical adsorption of the anti-CRP monoclonal antibody onto a poly-3-hexyl thiophene (P3HT) organic semiconductor surface. A supplementary nonionic hydrophilic polymer is used as a blocking agent preventing nonspecific interactions and allowing a better orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 31 publications
0
78
0
Order By: Relevance
“…The rapidly developing immunosensors (antibody–antigen sensors) have been actively applied in such fields as food, industry, environmental monitoring, and clinical examinations due to their high specificity, sensitivity, and stability . Lee et al first demonstrated PEDOT:PSS‐based OECTs for prostate specific antigen (PSA) detection .…”
Section: Integration Of Biomacromolecules Into Otft‐based Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapidly developing immunosensors (antibody–antigen sensors) have been actively applied in such fields as food, industry, environmental monitoring, and clinical examinations due to their high specificity, sensitivity, and stability . Lee et al first demonstrated PEDOT:PSS‐based OECTs for prostate specific antigen (PSA) detection .…”
Section: Integration Of Biomacromolecules Into Otft‐based Sensorsmentioning
confidence: 99%
“…These as‐fabricated biosensors showed a high affinity constant of ≈1.1 × 10 7 m −1 at pH 7 with a high degree of charge discrimination, surpassing the available optical detection technique and holding great potential in antibody screening and other biomedical applications. An important protein called C‐reactive protein (CRP), which plays an important protecting role in innate immunity of living organisms, was detected by low‐voltage P3HT‐based electrolyte‐gated OFETs (EGO‐FETs) . Note that a hydrophobic blocking polymer layer was additionally used to limit the nonspecific interactions and enable a better orientation of immobilized anti‐CRP antibodies.…”
Section: Integration Of Biomacromolecules Into Otft‐based Sensorsmentioning
confidence: 99%
“…FET is very sensitive to changes in local electric properties induced by small variations on the material surface. Hence, various 2D nanomaterials with superior electric properties, such as: silicon nanowires, carbon nanotubes, metal oxides, and organic semiconductors, have been integrated into FET protein sensors . For example, Pui et al demonstrated a silicon‐nanowire FET biosensor for real‐time measurement of tumor necrosis factor‐alpha (TNF‐α) and interleukin‐6 (IL‐6) secreted from macrophages .…”
Section: Biosensors For Label‐free Detection Of Single‐cell Protein Smentioning
confidence: 99%
“…C-reactive protein was ultrasensitively detected by a FET immunosensor based on an organic semiconductor surface composed of poly-3-hexyl thiophene (P3HT) [89]. Monoclonal anti-CRP antibodies were immobilized by physical adsorption onto the gate without any previous surface treatment.…”
Section: Other Nanomaterials/other Reports Of Interestmentioning
confidence: 99%